More than food production: Assemblages of values underpinning women‐led agroecological initiatives - Beatriz Vizuete; Milena Gross; Marina García‐Llorente; Elisa Oteros‐Rozas; Berta Martín‐López (People and Nature)
Abstract Agroecology advocates the transformation to sustainable agri‐food systems by renouncing production maximization and holistically integrating ecological and social aspects. The new peasantry fosters such sustainable agri‐food systems based on agroecological principles, driven by values of care for nature and people. In fact, values ascribed to nature can be pivotal in promoting sustainable agri‐food systems. Exploring which values, that is intrinsic, instrumental, and relational values, underpin agroecological initiatives and how they are assembled in farming practices could hold promise for moving towards agroecological transitions. We performed semi‐structured interviews with 15 new peasantry women who were active managers of agroecological initiatives in rural areas of the Madrid region, Spain. We found that new peasantry women expressed plural values of nature and frequently mentioned the relational values of meaningful occupation, care of nature and stewardship, and social relations. Values were articulated in three assemblages in which the (in‐)dependency of the values differed: co‐occurrence, bundling and blending. In co‐occurrence, the values coexisted without relating to each other. In bundling, the values were linked creating a narrative but their existence does not depend on each other. In blending, the values were mutually dependent. We found that instrumental and relational values often blended. We conclude that the plural and assembled appearance of values align with agroecological principles, being key to achieving bottom‐up agroecological transitions that care and have a sense of duty for biodiversity and fellow humans. Read the free Plain Language Summary for this article on the Journal blog.